2020
DOI: 10.1186/s12885-020-06959-2
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of risk stratified screening into the NHS breast screening Programme: views from British-Pakistani women

Abstract: Background: UK national guidelines suggest women at high-risk of breast cancer should be offered more frequent screening or preventative medications. Currently, only 1 in 6 high-risk women are identified. One route to identify more high-risk women is via multifactorial risk assessment as part of the UK's NHS Breast Screening Programme (NHSBSP). As lower socioeconomic and minority ethnic populations continue to experience barriers to screening, it is important that any new service does not exacerbate issues fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 34 publications
2
59
0
Order By: Relevance
“…Communication around such changes to breast screening, that could be considered de-implementation of a service, should however be carefully handled especially to minimise misunderstanding, as highlighted in interviews with UK screening figures and screening professionals [ 16 , 17 ]. In addition, communication materials should be developed in consideration of the ethnic diversity of the population likely to be invited given that previous research identified that British-Pakistani women were enthusiastic about risk-stratified screening [ 34 ] although described barriers to attending the NHSBSP including lack of knowledge about breast screening [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication around such changes to breast screening, that could be considered de-implementation of a service, should however be carefully handled especially to minimise misunderstanding, as highlighted in interviews with UK screening figures and screening professionals [ 16 , 17 ]. In addition, communication materials should be developed in consideration of the ethnic diversity of the population likely to be invited given that previous research identified that British-Pakistani women were enthusiastic about risk-stratified screening [ 34 ] although described barriers to attending the NHSBSP including lack of knowledge about breast screening [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important given the high educational attainment of the present sample as evidence suggests lower uptake and poorer understanding of risk is associated with socioeconomic status, such as qualifications [ 36 ]. Future research should be conducted with women from diverse backgrounds as although previous research highlighted that British-Pakistani women were interested in breast cancer risk assessment, including many where English was a second language, views may vary across other ethnic groups [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we explored RSBS as a whole, rather than focusing on a specific risk level [ 26 ] or ethnic group [ 32 ], we were able to identify three distinct responses to the concept. Previous research has demonstrated significantly greater acceptability for high-risk over low-risk screening options [ 11 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women from low SES and non-White ethnic backgrounds traditionally associated with non-engagement with the NHSBSP [ 37 ] were under-represented in our sample and may have different views. Consequently, further research is required to explore the attitudes of ‘hard to reach’ populations towards PRA and RSBS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developing BC-Predict, interviews with a cohort of British-Pakistani women from low socioeconomic backgrounds found that views toward risk-stratified screening are favourable. However, as with the present screening programme language barriers could still prevent access and reduce women's ability to make informed decisions [27]. Given this, in the present study we will assess whether women from low socioeconomic status backgrounds are less likely to take up the offer of riskstratified screening.…”
Section: Introductionmentioning
confidence: 98%